From Xizang to Xinjiang: An Analysis of the Role of Diaspora-Based Transnational Social Movements in Opposing Chinese Ethnic Minority Treatment - Marabini San Martín, Blanca (Sociología Histórica, 2022)
During the last few decades, the world has seen a significant rise in China’s international clout and, consequently, key international powers and actors have shifted their approach in engaging with the Asian giant, particularly regarding issues that China itself presents as internal or pertaining to national sovereignty. This article pursues an inquiry into the relationship between one such issue, Chinese ethnic minority treatment, and another recent shift in international context: the increased relevance of international forces and pressures originated by transnational social movements founded by ethnic minority members who have chosen to leave China. In order to do so, the diasporas of two ethnic minorities will be studied: the Tibetan minority residing in the Xizang Autonomous Region and the Uyghur minority in the Xinjiang Uyghur Autonomous Region of China. This includes a study of the forms of international resistance in which diaspora members are involved, as well as of the ability of diaspora-based transnational social movements to influence public opinion, state policies, and international organization positions in favor of their ethnic group.